Alignment of K‐8 mathematics interventions with strands of mathematical proficiency in meta‐analytic research. Issue 6 (16th March 2022) - Pulles, Sandra M.; Burns, Matthew K.
Abstract: The purpose of this paper was to examine current mathematics interventions designed for students in kindergarten through eighth grade to determine how often they incorporated the five strands of mathematical proficiency identified by the National Research Council (2001). The five strands are conceptual understanding, procedural knowledge, strategic competence, adaptive reasoning, and productive disposition. A systematic review of the literature resulted in 13 meta‐analyses of that studied a total of 19 unique interventions. The five strands of mathematical proficiency were then compared to each intervention to determine with which strand(s) the intervention aligned. None of the 19 interventions contained all five strands, but interventions could be combined to enhance math proficiency. The strands of mathematics proficiency could provide a framework with which to meaningfully combine intervention components. HIGHLIGHTS: A review of 19 math interventions found that none of them addressed all five strands of proficiency, and it would require combinations of them to do so. The strands of math proficiency could provide a framework for intervention decisions in math.